Union of the Comoros : Poverty Reduction Strategy Paper: Review of the Second Year of Implementation. (IMF Staff Country Reports; Country Report ;, 2013)
Since its independence in 1975, the Union of Comoros has been deeply affected by political and institutional crises. Resolution of the separatist crisis on the island of Anjouan and subsequent national consolidation has constituted a historic turning point. The government has begun a wide-ranging program of structural reforms. The external debt of Comoros remains unsustainable. The government is making efforts to speed up the implementation of reforms and obtain access to a reduction in its debt burden.